Growth potential limits drought morphological plasticity in seedlings from six Eucalyptus provenances - Maseda, Pablo H. (2015)
Water stress modifies plant above- vs belowground biomass allocation, i.e., morphological plasticity. It is known that all species and genotypes reduce their growth rate in response to stress, but in the case of water stress it is unclear whether the magnitude of such reduction is linked to the genotype's growth potential, and whether the reduction can be largely attributed to morphological adjustments such as plant allocation and leaf and root anatomy. We subjected seedlings of six seed sources, three from each of Eucalyptus camaldulensis (potentially fast growing) and E. globulus (inherently slow growing), to three experimental water regimes. Biomass, leaf area and root length were measured in a 6-month glasshouse experiment. We then performed functional growth analysis of relative growth rate (RGR), and aboveground (leaf area ratio (LAR), specific leaf area (SLA) and leaf mass ratio (LMR)) and belowground (root length ratio (RLR), specific root length (SRL) and root mass ratio (RMR)) morphological components. Total biomass, root biomass and leaf area were reduced for all Eucalyptus provenances according to drought intensity. All populations exhibited drought plasticity, while those of greater growth potential (RGRmax) had a larger reduction in growth (discounting the effect of size). A positive correlation was observed between drought sensitivity and RGRmax. Aboveground, drought reduced LAR and LMR; under severe drought a negative correlation was found between LMR and RGRmax. Belowground, drought reduced SRL but increased RMR, resulting in no change in RLR. Under severe drought, a negative correlation was found between RLR, SRL and RGRmax. Our evidence strongly supports the classic ecophysiological trade-off between growth potential and drought tolerance for woody seedlings. It also suggests that slow growers would have a low capacity to adjust their morphology. For shoots, this constraint on plasticity was best observed in partition (i.e., LMR) whereas for roots it was clearest in morphology/anatomy (i.e., SRL). Thus, a low RGRmax would limit plastic response to drought not only at the whole plant level but also at the organ and even the tissue level.